Análise experimental comparativa dos parâmetros de fabricação de filmes finos a base de Cr e Mo com uma composição gradual de Si para aplicações em absorvedores solares seletivos - Venâncio, Raissa (2022)
The use of solar energy for application in solar thermal heating systems has grown exponentially due to the inclusion of renewable sources in the traditional energy matrix. From this perspective, one of the research strands aims to improve the efficiency of these systems through the optimization of solar collectors. In this work, the objective is to optimize the process of obtaining selective surfaces for solar collectors, comparing the optical parameters of coatings based on Cr and Mo with a gradual layer of Si manufactured by the sputtering technique (Magnetron Sputtering). with different deposition parameters. The coatings were deposited on AISI 304 stainless steel substrates with two types of treatment (hexane cleaning and electropolishing) and four different compositions: Mo, Cr, Mo + Si and Cr + Si formed from three different times (10, 20 and 30 min) of sputtering, totaling 24 samples produced in triplicate. The coatings were submitted to Optical Profiling, UV-Vis-NIR Spectrophotometry, Fourier Transform Infrared Spectrophotometry (FTIR), X-Ray Excited Photoelectron Spectroscopy (XPS), one-way statistical analysis of variance (ANOVA) and electrochemical corrosion. The results indicated that the Magnetron Sputtering deposition technique is effective in the production of thin films with extreme uniformity and reproducibility, the deposition time, the type of material and the treatment affect the absorption performance of the film. All films produced showed high values of mean solar absorbance (above 87%) to be considered Selective Solar Surfaces (85%). The electropolishing treatment showed the lowest standard deviation in film production (between 0.7 – 2.0) with absorption results above 95%. The Cr + Si and Mo + Si films, on electropolished substrates, obtained with 20 minutes of spraying obtained the best absorption performance with 98.7% and 98.4%, respectively. Through the Profilometry analysis, it can be observed that the less rough surfaces favored the absorbing property of the films and the morphological profiles showed very uniform surfaces with thickness in the order of micrometers. Through FTIR and XPS analysis, it was possible to identify the oxidation of the film-forming compounds. The analysis of variance highlighted that the substrate treatment is the most statistically significant factor for absorbance and roughness, while the deposition time affects the thickness of the films. The corrosive test showed that the Cr and Cr/Si films showed higher polarization resistivities. The Cr/Si film with 20 minutes of deposition on electropolished substrate presents the best configuration for selective solar surfaces.